Gaming disorder: its delineation as an important condition for diagnosis, management, and prevention - Saunders, John B.; Mann, Karl; Fauth-Bühler, Mira; Rumpf, Hans-Jürgen (Journal of behavioral addictions, 2017)
Online gaming has greatly increased in popularity in recent years, and with this has come a multiplicity of problems due to excessive involvement in gaming. Gaming disorder, both online and offline, has been defined for the first time in the draft of 11th revision of the International Classification of Diseases (ICD-11). National surveys have shown prevalence rates of gaming disorder/addiction of 10%-15% among young people in several Asian countries and of 1%-10% in their counterparts in some Western countries. Several diseases related to excessive gaming are now recognized, and clinics are being established to respond to individual, family, and community concerns, but many cases remain hidden. Gaming disorder shares many features with addictions due to psychoactive substances and with gambling disorder, and functional neuroimaging shows that similar areas of the brain are activated. Governments and health agencies worldwide are seeking for the effects of online gaming to be addressed, and for preventive approaches to be developed. Central to this effort is a need to delineate the nature of the problem, which is the purpose of the definitions in the draft of ICD-11.